Performance Assessment of a Multi-energy System for a Food Industry. (December 2015) - Biglia, Alessandro; Fabrizio, Enrico; Ferrara, Maria; Gay, Paolo; Aimonino, Davide Ricauda
Abstract: The energy saving is becoming an important topic also in the food industry. For this reason, it is important to use multi-energy systems to produce hot water for processes and space heating. The application considered in this paper, which concerns a chocolate factory, focuses on the hot water production through a multi-source storage tank. The water inside the tank is heated by four solar panels when there is enough solar radiation and by a gas back-up boiler. The cold aqueduct water, which it is going to be heated in the accumulator, is first preheated recovering waste heat from the condenser of the chiller. The system was equipped with an energy monitoring and recording device. The thermal model was used to analyse the hot water production system during the summer season considering the options of the heat recovery and of the solar thermal exploitation. The performance analysis was developed in order to establish energy savings that may be achieved.